(untitled) - Sharf, Richard S.; Richard S. Sharf (Belmont, CA, 2006)
A must read for practicing counselors and counselors in training, APPLYING CAREER DEVELOPMENT THEORY TO COUNSELING shows you how to apply principles of career development in a counseling setting! A clear writing style, useful case examples, and integrated coverage of diversity set this text apart from others in the field. The book-specific website makes studying easy with discussion questions, tutorial quizzes, and relevant links
Keywords: Vocational guidance; Career development